Overview of Soil Water Tax Collection in Bandung Regional Financial Agency - Tresnawati, Rina; Gusnandar Arnan, Sendi; Suryana (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to find out the basis for the imposition and procedure for collecting groundwater tax in the Revenue Division of Bandung Regency. Groundwater tax is the type of tax that has the largest arrears compared to other types of taxes. The total tax arrears are more than 30 industrial companies with highly varied tax arrears. The water acquisition value is the basis for taxing groundwater. The research method used in this research is the descriptive method. The results showed that groundwater tax collection performed by the Bandung Regency Revenue Division I was in accordance with Regional Regulation No. 01 of 2011 concerning local taxes and Regent Regulation Number 42 of 2016 concerning technical guidelines for water tax collection. Barriers to groundwater tax collection include the slow calculation of the water acquisition value and the incompatibility of the amount of tax owed by the amount of tax calculated by the taxpayer.